IMPLEMENTASI PROGRAM KAMPUS MENGAJAR DALAM MENUMBUHKAN MINAT BELAJAR SISWA SEKOLAH MENENGAH PERTAMA SMPK SWADAYA TUAKEPA - Fransiska Jone Mare; Bartoldus Sora Leba (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Schools in remote areas still face various challenges in meeting students' learning needs, particularly regarding literacy, numeracy, and technological adaptation. This community service activity aims to observe real conditions in the field and to formulate program concepts that address the identified issues based on the needs of students at the target schools. The method employed is qualitative with a descriptive approach. Data collection techniques include observation and interviews. The results of this activity include the development and implementation of work programs designed to address the literacy, numeracy, and technological skills needs of students and schools. The programs implemented have shown positive impacts, such as increasing students' learning motivation and abilities and creating a more conducive and inspiring learning atmosphere within the school environment.